Enhancing abiotic stress resilience in Eruca sativa: the synergistic role of extremophilic microbial inoculants and crystalline zinc oxide - Assis, Amanda Stefanie Jabur de (Universidade Federal de São Carlos, 2026)
Abiotic stresses such as salinity, water deficit, and high solar radiation constitute important limitations for plant establishment and agricultural productivity. Extremophilic microorganisms, adapted to harsh environments, have physiological characteristics that can be exploited to mitigate these stresses in plants. This thesis investigates the potential of extremophilic microorganisms isolated from photovoltaic panels to improve the plant performance of arugula (Eruca sativa) seedlings under abiotic stress, with emphasis on the interaction of these microorganisms with crystalline zinc oxide (ZnO). Initially, the ultraviolet radiation resistance of bacterial and yeast isolates from photovoltaic panels was evaluated, showing contrasting tolerance profiles, with Rhodotorula mucilaginosa standing out as highly resistant to UV radiation. Next, strains with better performance were applied to Eruca sativa seeds to evaluate their effects on the percentage and speed of germination under saline and osmotic stress, in the presence or absence of ZnO. Finally, the effects of microbial inoculation with Arthrobacter koreensis and ZnO on seedling growth and responses to abiotic stresses (lengths, biomass allocation, leaf area) were analyzed. The results demonstrate that extremophilic microorganisms can improve germination and seedling performance under abiotic stress in a strain- and environmental context-dependent manner. Supplementation with ZnO consistently amplified the microbial effects, especially under severe stress conditions. Instead of promoting uniform growth, microbial inoculation contributed to greater growth stability and stress tolerance. This work highlights the potential of combining extremophilic microorganisms and inorganic cofactors as a sustainable strategy to improve plant establishment in agricultural environments subject to environmental stresses.
Enhancing abiotic stress resilience in Eruca sativa: the synergistic role of extremophilic microbial inoculants and crystalline zinc oxide
Keywords: Condicionamento microbiano; Óxido de Zinco; Eruca sativa; microbial priming; zinc oxide; Eruca sativa; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; 2. Fome Zero e Agricultura Sustentável